Analisis Jaringan Komunikasi Dalam Diseminasi Informasi Produksi Dan Pemasaran Jeruk Pamelo (Communication Network Analysis in Dissemination of Pummelo Fruits Production and Marketing Information) - Alfi Rahmawati; Pudji Muljono; Sarwititi Sarwoprasodjo (Institut Pertanian Bogor, 2016)
Pummelo farmers need production technology and marketing information to optimize their capability and agricultural productivity. Communication process to disseminate information about pummelo nursery, maintanance, and marketing between farmers and external stakeholder will build a communication network. The purpose of this study is to analyze communication structure in dissemination of pummelo nursery, maintanance, and marketing information; identified main actors in the networks; analyze correlation between farmer characterctics and communication network analysis, and correlation between communication network analysis with the effectiveness of information dissemination. The result of this study shows that extension worker are the main actor in disseminationof pummelo nursery and maintanance information network, and whole seller is the main actor in dissemination of marketing information network. There’s no significantly correlation between farmers characteristics and communication network analysis in dissemination of pummelo nursery, maintanance, and marketing information, except cosmopolity variable and outdegree centrality in dissemination of pummelo maintanance information. In addition, there’s no significatly correlation between communication network analysis variables and effectiveness dissemination of information in production and marketing network.Keywords: communication process, farmers, network